2002
DOI: 10.1002/neu.10086
|View full text |Cite
|
Sign up to set email alerts
|

Intraneuronal amyloid precursor protein (APP) and appearance of extracellular β‐amyloid peptide (aβ) in the brain of aging kokanee salmon

Abstract: Antibodies to human amyloid precursor protein (APP(695)) and beta-amyloid peptide (A beta(1-42)) were used to determine timing of amyloidosis in the brain of kokanee salmon (Oncorhynchus nerka kennerlyi) in one of four reproductive stages: immature (IM), maturing (MA), sexually mature (SM), and spawning (SP), representing a range of aging from somatically mature but sexually immature to spawning and somatic senescence. In IM fish, immunoreactive (ir) intracellular APP occurred in 18 of 23 brain regions. During… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 78 publications
0
22
0
Order By: Relevance
“…. White dot at base of a "percent pyknotic" bar means that the initial A␤ deposition appeared at that stage (from Maldonado et al, 2002). No A␤ deposition occurred in the Dp.…”
Section: Neurodegeneration In the Entire Salmon Brainmentioning
confidence: 96%
See 2 more Smart Citations
“…. White dot at base of a "percent pyknotic" bar means that the initial A␤ deposition appeared at that stage (from Maldonado et al, 2002). No A␤ deposition occurred in the Dp.…”
Section: Neurodegeneration In the Entire Salmon Brainmentioning
confidence: 96%
“…Maldonado et al (2000b) reported that brains of spawning but not immature kokanee salmon exhibit extracellular deposits of ␤-amyloid (A␤) peptide as well as senile A␤-plaques similar to those described in aging humans. Furthermore, the amount of A␤ increased with reproductive stage (Maldonado et al, 2002). However, it is not clear if neurodegeneration is positively correlated with this amyloidosis in the senescent salmon brain.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, elevations in post-reproductive LH may drive neurological and vascular diseases while The large dyotic signaling in salmon (and other semelparous species) post-reproduction leads to dramatic and rapid (within 1-3 weeks) changes in tissue structure and function (phenoptosis) that are similar to the degenerative changes found in other aging vertebrates, including humans: the brain (amyloidosis), liver, stomach (peptic ulcers), spleen, thymus, thyroid, pituitary, kidney, and cardiovascular system exhibit degenerative changes, the adrenocortical tissue and pancreas display hyperplasia, and immune system collapse results in skin infections (Dickhoff et al 1989;Maldonado et al 2000Maldonado et al , 2002aWexler 1960, 1962). At this time, the suppression by 17β-estradiol on the utilization of pregnenolone as a substrate for cortisol synthesis by the interrenals (adrenals) is lost (McQuillan et al 2003).…”
Section: Ratio Of Sex Steroid/gonadotropin As a Measure Of Dyotic Sigmentioning
confidence: 96%
“…SAA is highly conserved between fish and humans (Lashuel, 2008), and aging Pacific salmon undergo a rapid senescence with accompanying A amyloid build-up in their brains (Maldonado, Jones and Norris, 2002), but apparently only one report of systemic amyloidosis in fish appears in the literature and the muscles did not seem affected (Mashima, Cornish and Lewbart, 1997). Liver involvement raised the possibility that a product such as cod liver oil could potentially be contaminated, but protein fractions should largely be purified out of fish oil preparations.…”
Section: Other Dietary Sources Of Amyloid Fibrilsmentioning
confidence: 99%